Prevalence of depression and anxiety among myasthenia gravis (MG) patients: A systematic review and meta‐analysis. Issue 1 (10th December 2022) - Nadali, Javad; Ghavampour, Neda; Beiranvand, Farzaneh; Maleki Takhtegahi, Mona; Heidari, Mohammad Eghbal; Salarvand, Shahin; Arabzadeh, Tina; Narimani Charan, Omid
Abstract: Objective: Myasthenia gravis (MG) people experience adverse psychiatric outcomes, which may impact on their life and disturb their daily activity. Depression and anxiety are identified as significant psychiatric problems that MG people face. However, there is no sufficient epidemiological information about depression and anxiety‐based publication. Due to this limitation, the aim of this study was to review the prevalence of depression and anxiety in MG patients. Methods: Original and international databases were searched to find papers about the estimation of anxiety and depression. Random‐effects analysis was used for calculating the proportions of anxiety and depression. For estimating anxiety and depression based the severity, instruments, type of studies, and study regions, subgroup analysis was performed. Results: 38 studies met inclusion criteria and entered study. The pooling of the prevalence of depression was found at 36%, (95% CI 28% to 45%). Also, prevalence of anxiety was found at 33%, (95% CI 25% to 42%). Prevalence of depression based on mild, moderate, and severe level was 27%, 14%, and 9%, respectively. Conclusions: Anxiety and depression are a major concern among MG individuals. The estimation of both anxiety and depression are high even when compared to other autoimmune diseases. It seems depression and anxiety are important issues and more attention needs to be paid to these psychiatric disorders. Abstract :